Epoxy Chip-in-Carrier Integration and Screen Printed Metallization for Multichannel Microfluidic Lab-on-CMOS Microsystems - Li, Lin (IEEE Trans Biomed Circuits Syst, 2018)
The integration of biosensors, microfluidics and CMOS instrumentation provides a compact lab-on-CMOS microsystem well suited for high throughput measurement. This paper describes a new epoxy chip-in-carrier integration process and two planar metallization techniques for lab-on-CMOS that enable on-CMOS electrochemical measurement with multichannel microfluidics. Several design approaches with different fabrication steps and materials were experimentally analyzed to identify an ideal process that can achieve desired capability with high yield and low material and tool cost. On-chip electrochemical measurements of the integrated assembly were performed to verify the functionality of the chip-in-carrier packaging and its capability for microfluidic integration. The newly developed CMOS-compatible epoxy chip-in-carrier process paves the way for full implementation of many lab-on-CMOS applications with CMOS ICs as core electronic instruments.